2020
DOI: 10.3390/ijms21207715
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Piper sarmentosum Aqueous Extract as a Bone Protective Agent, a Histomorphometric Study

Abstract: Glucocorticoids are one of the causes of secondary osteoporosis. The aqueous extract of Piper sarmentosum contains flavonoids that possess antioxidant effects. In this study, we determined the effects of aqueous Piper sarmentosum leaf extract on structural, dynamic and static histomorphometric changes from osteoporotic bones of rats induced with glucocorticoids. Thirty-two Sprague-Dawley rats were divided equally into four groups—Sham control group given vehicles (intramuscular (IM) olive oil and oral normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Ps had a high phenolic content in both aqueous and boiled aqueous extractions [4]. Our previous study showed that Ps aqueous extract assist in osteoporotic fracture healing [12], strengthen the bone biomechanical properties [14], increased the osteoprotegerin (OPG) gene expression that modulate the RANKL-OPG pathway of bone remodelling [16] and improved the histomorphometry parameters [25].…”
Section: Resultsmentioning
confidence: 99%
“…Ps had a high phenolic content in both aqueous and boiled aqueous extractions [4]. Our previous study showed that Ps aqueous extract assist in osteoporotic fracture healing [12], strengthen the bone biomechanical properties [14], increased the osteoprotegerin (OPG) gene expression that modulate the RANKL-OPG pathway of bone remodelling [16] and improved the histomorphometry parameters [25].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in order to further confirm the results of the network pharmacology analysis, experimental verification was carried out using a postmenopausal osteoporotic mouse model. The structural and static histomorphometry parameters measure the microstructure and cellular components of the trabecular bone, respectively [ 55 ]. Micro-CT and H&E staining revealed that the trabecular bone levels of the distal femur of mice increased after gavage with velvet antler.…”
Section: Discussionmentioning
confidence: 99%
“…The high content of compounds in P. sarmentosum enables it to possess numerous properties such as antibacterial, antihypertensive, antihyperglycemic and antimalarial properties and tissue regeneration of embryos and caudal fins [ 6 , 7 , 8 ]. Previous in vivo studies have shown that P. sarmentosum extracts exhibited the ability to act as a bone protective agent by restoring the microstructure and bone mass in glucocorticoid-induced osteoporosis and in ovariectomized and adrenalectomized rats [ 9 , 10 ]. These health benefits are attributed to the synergistic effect of compounds abundantly found in the raw plant extract.…”
Section: Introductionmentioning
confidence: 99%